\(\frac{2x-\sqrt[]{x^2}-1}{3x^2-4x+1}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 2 2019

\(\frac{2x-x-1}{3x^2-3x-x+1}\)

\(=\frac{x-1}{\left(x-1\right)\left(3x-1\right)}\)

\(=\frac{1}{3x-1}\)

10 tháng 8 2015

\(\sqrt{\left(3x+2\right)^2}=\left|3x+2\right|\)

\(\sqrt{4x^2+4x+1}=\sqrt{\left(2x+1\right)^2}=\left|2x+1\right|\)

\(\sqrt{\frac{x^2-2x+1}{x-1}}=\sqrt{\frac{\left(x-1\right)^2}{x-1}}=\sqrt{x-1}\)

12 tháng 6 2017

a)   \(2x-\sqrt{4x^2+4x+1}=2x-\sqrt{\left(2x+1\right)^2}=2x-\left|2x+1\right|\)

Vì   \(x< -\frac{1}{2}\)nên   \(\left|2x+1\right|=-\left(2x+1\right)\)

\(\Rightarrow2x+2x+1=4x+1\)

b) \(3x+2-\sqrt{9x^2-12x+4}=3x+2-\sqrt{\left(3x-2\right)^2}=3x+2-\left|3x-2\right|\)

Khi   \(x\ge\frac{2}{3}\)thì   \(\left|3x-2\right|=3x-2\)

\(\Leftrightarrow3x+2-\left|3x-2\right|=3x+2-3x+2=4\)

Khi     \(x< \frac{2}{3}\)  thì  \(\left|3x-2\right|=2-3x\)

\(\Leftrightarrow3x+2-\left|3x-2\right|=3x+2-\left(2-3x\right)=6x\)

c)  \(\sqrt{9a}-\sqrt{16a}+\sqrt{49a}=3\sqrt{a}-4\sqrt{a}+7\sqrt{a}\)

Đặt   \(\sqrt{a}=x\)  ta được :  \(3x-4x+7x=6x\)\(=6\sqrt{a}\)( Do  \(a\ge0\))

d)  \(\sqrt{160a}+2\sqrt{40a}-3\sqrt{90a}=4\sqrt{10a}+4\sqrt{10a}-9\sqrt{10a}\)\(=-\sqrt{10}\)

TK NKA !!!

10 tháng 10 2019

Câu 1: Sửa lạ đề chút nhé : 4x + 1  -> 4x -1 

 Đặt A = \(\sqrt{2x+\sqrt{4x-1}}+\sqrt{2x-\sqrt{4x-1}}\)

=>  \(\sqrt{2}.A\)= ​\(\sqrt{4x-1+2\sqrt{4x-1}+1}+\sqrt{4x-1-2\sqrt{4x-1}+1}\)

\(\sqrt{\left(\sqrt{4x-1}+1\right)^2}+\sqrt{\left(\sqrt{4x-1}-1\right)^2}\)

\(\left|\sqrt{4x-1}+1\right|+\left|\sqrt{4x-1}-1\right|\)

Vì \(\frac{1}{4}< x< \frac{1}{2}\Rightarrow0< 4x-1< 1\Rightarrow0< \sqrt{4x-1}< 1\)

nên \(\sqrt{2}A=\)\(\sqrt{4x-1}+1+1-\sqrt{4x-1}\)=2

=> \(A=2:\sqrt{2}=\sqrt{2}\)

Câu 2. Có: \(9-4\sqrt{2}=8-2.2\sqrt{2}+1=\left(2\sqrt{2}-1\right)^2\)

=> \(\sqrt{9-4\sqrt{2}}=2\sqrt{2}-1\)

=> ​\(4+\sqrt{9-4\sqrt{2}}=4+2\sqrt{2}-1=2+2\sqrt{2}+1=\left(\sqrt{2}+1\right)^2\)

=> \(\sqrt{4+\sqrt{9-4\sqrt{2}}}=\sqrt{2}+1\)

=> \(53-20\sqrt{4+\sqrt{9-4\sqrt{2}}}=53-20\left(\sqrt{2}+1\right)=33-2.10\sqrt{2}=5^2-2.5.2\sqrt{2}+8=\left(5-2\sqrt{2}\right)^2\)

=> \(\sqrt{53-20\sqrt{4+\sqrt{9-4\sqrt{2}}}}=5-2\sqrt{2}\)

\(\sqrt{2x+\sqrt{4x-1}}+\sqrt{2x-\sqrt{4x-1}}\)

\(A=\left(\frac{\sqrt{x}-4x}{1-4x}-1\right):\left(\frac{1+2x}{1-4x}-\frac{2\sqrt{x}}{1-4x}-\frac{2\sqrt{x}}{2\sqrt{x}-1}-1\right)\)

\(=\left(\frac{\sqrt{x}-4x-1+4x}{1-4x}\right):\left(\frac{1+2x-2\sqrt{x}-2\sqrt{x}\left(2\sqrt{x}+1\right)-1+4x}{1-4x}\right)\)

\(=\frac{\sqrt{x}-1}{1-4x}:\frac{2x-4\sqrt{x}}{1-4x}=\frac{\sqrt{x}-1}{1-4x}.\frac{1-4x}{2\sqrt{x}\left(\sqrt{x}-1\right)}=\frac{1}{2\sqrt{x}}\)

b, \(A>A^2\Rightarrow\frac{1}{2\sqrt{x}}>\left(\frac{1}{2\sqrt{x}}\right)^2\Rightarrow\frac{1}{2\sqrt{x}}>\frac{1}{4x}\Rightarrow\frac{1}{2\sqrt{x}}-\frac{1}{4x}>0\Rightarrow\frac{2\sqrt{x}-1}{4x}>0\)

\(2\sqrt{x}-1>0\);\(4x>0\)

\(\Rightarrow x>0\)thì \(A>A^2\)